Konsumsi Pakan dan Bobot Panen Ayam Broiler yang Diberi Pakan Antibiotic Growth Promoters dan Non Antibiotic Growth Promoters Pada Kandang Tertutup - Cika Firdausi Pikana Utami; Elly Tugiyanti; Emmy Susanti (ANGON: Journal of Animal Science and Technology, 2020)
Background. This Study is entitled "Consumption of Feed and Harvest Weights of Broilers Given Antibiotic Growth Promoters and Non Antibiotic Growth Promoters Weight in a Closed Cage". Materials and methods. This research was conducted in 3 areas, namely Banyumas, Purbalingga, and Cilacap in December 2019. This study aims to determine the relationship of feed consumption and harvest weight of broilers fed with Antibiotic Growth Promoters and Non Antibiotic Growth Promoters in closed cages. The research method used was a survey with the aim of the research being broiler chicken breeders who became a partnership with PT Cemerlang Poultry Lestari with ownership of broiler totaling 10,000-50,000 in closed cages. Results. Average feed consumption with Antibiotic Growth Promoters in a closed cage in one periode to get results 3,27±0,56 kg/tail, while the average consumption of feed with Non Antibiotic Growth Promoters in a closed cage in one periode to get results 3,16±0,48 kg/tail (P</>0.05). Harvest weights with Antibiotic Growth Promoters in a closed cage in one periode get a result of 1,95±0.23 kg/tail, while the average weight of the harvest with Non Antibiotic Growth Promoters in a closed cage in one periode get a result of 1.91±0.28 kg/tail (P</>0.05). Conclusion.The conclusion of this study is that feed with Antibiotic Growth Promoters and feed with Non Antibiotic Growth Promoters were not significantly different from feed consumption and harvest weight of broiler chickens.